Calibration of vehicle dynamics and stability control model. (2016) - Zhou, Xianjie; Venhovens, Paul
This publication describes a process to develop and calibrate a physics-based model for vehicle stability control. The approach consists of two phases. In the first phase, a baseline vehicle dynamics model was established using the commercially available simulation tool CarSim. The model was calibrated and validated for a variety of steady state, transient state and brake intervention handling manoeuvres using experimental test data. In the second phase, a simplified stability control model was developed in Matlab/Simulink based on representative control strategies. Subsequently, the vehicle dynamics model and stability control model developed were coupled using co-simulation and calibrated such that the closed-loop system behaviour approximated the real world test behaviour as best as possible. Finally, two case studies were developed to showcase the application of the closed-loop mathematical model in simulation-based studies addressing aftermarket vehicle modifications and their implication on vehicle stability control behaviour.